MHT vs. veins: is there any reason to fear? - Stachowiak, Grzegorz (Menopause Review/Przegląd Menopauzalny, 2013)
Venous thromboembolism (VTE) is both a contraindication and a complication of menopausal hormone therapies (MHT). This article presents a review of up-to-date literature on VTE epidemiology and its risk factors, paying attention mostly to the impact of MHT on VTE risk, starting from the 1970s reports to the North American Menopause Society position statement of 2012. The risk of VTE is minimized by the proper patients’ qualification (e.g. elimination of risk factors, 50-59-aged patients), choice of transdermal MHT, hormone dose reduction and proper progestogen choice.